Students’ English-medium instruction motivation in three English-medium instruction courses in China - Zhang, Mengjia; Pladevall-Ballester, Elisabet (Frontiers in Psychology, 2023)
EMI (English-medium instruction) has been spreading rapidly as the result of China’s movement to internationalize its HEIs (higher education institutions). However, there is a dearth of research studies on students’ motivation in EMI contexts, which should not only explore students’ Foreign Language Learning (FLL) motivation in isolation but the highlights of integrating both content and language learning as a complex. This paper specifically reports on the development of students’ EMI motivation and anxiety over one semester and compares three disciplines: International Trade, Film Production, and Project Management. Pre-post questionnaires and post focus group interviews were administered to students. Results showed that students generally had high EMI motivation and anxiety though the levels decreased from pre to post phases. The International Trade group had greater motivation, particularly instrumental motivation. Findings are discussed in relation to the existing literature and the local context. Pedagogical and institutional-level implications for policies are also provided.